Implementasi Manajemen Persuratan Dalam Ketatausahaan di Sekolah SD Swasta Sejahtera - Harahap, Hasriyati; Tanjung, Rama Satya; Nurmaini, Ella; Darmansah, T. (Yayasan Daarul Huda Kruengmane, 2024)
The research that was prepared aims to discuss the implementation of correspondence management in administration at Sejahtera private SD schools, where this correspondence management can help educational staff manage all problems related to school administration. Correspondence management is an important element in school administration, playing a role in work efficiency, information security and accountability. This research discusses the implementation of correspondence management in schools, analyzing the practices implemented, the challenges faced, and strategies that can be taken to increase the effectiveness of the correspondence system. By using this research method, a descriptive qualitative research method is used through a literature review approach using book and journal reviews which are then analyzed and concluded from the research cited. It is hoped that the results of this research can contribute to schools in improving the effectiveness of correspondence management and creating a more orderly, efficient and transparent school administration.